The effect of pulse DC and DC substrate bias during in situ cleaning PVD process on surface roughness - Hanizam, Hashim; Mohd Saufhwee, Abd Rahman; Anuar, A.R, K.; Md. Nizam, Abd. Rahman, Dr.; Noraiham, Mohamad, Dr. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.